Pusat Tuisyen CGT Management System - Kamaruzzaman, Nabiha Aishah; Selamat, Norhanim (Applied Information Technology And Computer Science, 2025)
Tuition is a supplementary education service aimed at enhancing students’ academic performance by providing additional guidance and learning opportunities outside regular school hours. Pusat Tuisyen Cemerlang Gemilang Terbilang (CGT) currently faces challenges due to its reliance on manual processes for managing attendance, payment records, and class schedules. These inefficiencies result in increased administrative workload, data inaccuracies, and delays, impacting the overall user experience for teachers, students, and parents. To address these issues, an online management system has been developed, aiming to enhance efficiency and streamline processes. The system follows the prototyping software process model, encompassing phases such as planning, analysis, design, implementation, and testing. The management system is specifically designed for deployment at CGT, catering to the needs of its administrators, teachers, students, and parents. The expected outcomes include automated attendance tracking via QR codes, streamlined payment handling, user-friendly class scheduling, and real-time performance monitoring. By automating key operations, the system aims to enhance CGT’s overall efficiency and user satisfaction.